Effect of Micelle-Incorporated Cisplatin With Sizes Ranging From 8 to 40 nm for the Therapy of Lewis Lung Carcinoma - Wang, Zhicheng; Li, Yumin; Zhang, Tong; Li, Hongxia; Yang, Zhao; Wang, Cheng (Frontiers in Pharmacology, 2021)
Insufficient transport of therapeutic cargo into tumor bed is one bottleneck for cancer nanomedicine. Block copolymers are promising carriers with smaller particle size by ratio- modification. Here, we constructed cisplatin nanoparticles with sizes ranging from 10-40 nm to study the permeability and therapy of lewis lung carcinoma. We synthesized methoxy-poly (ethylene-glycol)2000-block poly(L-glutamic acid sodium salt)1979 loading cisplatin through complexation reaction. The cisplatin nanomedicine has high drug loading and encapsulation efficiency. In vitro data demonstrated that cisplatin nanoparticle had equivalent growth-inhibiting effect on Lewis lung carcinoma cells compared to free cisplatin. In vivo evidences showed cisplatin nanoparticle had superior antitumor effect on Lewis lung carcinoma mouse model with no obvious side effects. All results indicated that optimizing the ratio of block copolymer to obtain smaller sized nanomedicine could act as a promising strategy for overcoming the inadequate accumulation in poorly vascularized tumors.